Analyzing gender, health and communicable disease: guidelines from the Liverpool school of tropical medicine - Tolhurst, Rachel (1999)
Rachel Tolhurst uses a framework for the analysis of gender and health developed by the Liverpool School of Tropical Medicine (1999) to outline some of the ways in which gender relations and manifestations of globalization such as the liberalization and expansion of markets may interact to produce gender inequities in health, with a focus on communicable disease. - Reproduced
Keywords: Infectious diseases